DEVELOPINGASSESSMENT INSTRUMENTBASED QUIZSTARIN THEORY OF KINETIC GAS TO MEASURE COGNITIVE ABILITIES SENIOR HIGH SCHOOL STUDENTS - Hendra oktavianta; Edi Istiyono (Universitas negeri Yogyakarta, 2016)
This research aims to determine 1) the feasibility assessment instrument based Quizstar for measuring cognitive abilities of high school students, 2) mastery of the kinetic theory of gases learners. This research was the development of the model 4-D (Four D Models) in the opinion of Thiagarajan consisting of stages define, design, develop, and disseminate.The results of this study are: (1) assessment instrument based Quizstar feasible for measuring cognitive ability of learners to have met the content validity by expert judgment and has gained empirical evidence fit the Rasch models. The itemsdifficulty indexes were between -1.65 and 1.78, which means the items were good. Assessment instruments based Quizstar have had reliability coefficient of 0.73 that included reliable category. Based on the information function, assessment instruments very appropriately used to measure cognitive abilities of learners capable of -2.3 to 1.1. Assessment instruments based Quizstar get CVI value of 1.00 which included a very good category with the reliability of 0.868 which includes a very reliable category. The result analysis of learners questionnaire responses showed in enough, good, and very good categories respectively – were 11%, 52%, and 36%. (2) The ability of learners get less, enough, good, and very good category respectively – were 21%, 44%, 25% 9%.